Investigation of factors influencing the income of entrepreneurs in Cipondoh lake - Heny Ratnaningtyas; Nurbaeti Nurbaeti; Amrullah Amrullah (Universitas Merdeka Malang, 2023)
A sufficiently large working capital, a long-operating business, skilled and experienced employees, as well as determining the appropriate business opening and closing hours, all can increase the chances of getting more visitors, increasing customer trust, and higher business revenue. This study aims to determine the influence of working capital, number of employees, length of business operation, and working hours on the income of entrepreneurs in Danau Cipondoh. This research uses a quantitative descriptive type and the sampling technique used is saturated sampling. The population and sample size are both 63 entrepreneurs. The partial results of the study indicate that working capital and the number of employees do not have a significant effect on income. However, the length of business operation and working hours have a significant effect on income. Entrepreneurs in Danau Cipondoh do not have sufficient capital, but maintaining good product quality and service quality results in increased visitors and revenue. The length of business operation makes entrepreneurs more diligent in running their business and producing high work productivity and income. With sufficient skilled workers, the business can run well, leading to an increase in sales volume and revenue. Extending working hours has an impact on increasing sales volume and revenue. The implications of this study are: (1) Entrepreneurs need to manage working capital well, improve efficiency, and productivity; (2) Tourism destination managers need to improve infrastructure, facilities, and promotion; (3) The government of Tangerang Kota needs to provide training, mentoring, financing, facilities, and supervision for business activities.